2018
DOI: 10.1007/s00268-018-4734-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Preoperative Frailty Models in Predicting Postoperative Outcomes in Geriatric General Surgical Patients

Abstract: FP was associated more consistently than CGA with adverse postoperative outcomes in elderly patients undergoing general surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Moreover, the functional independence and the comorbidities of the patients are outweighed by ASA physical status which largely includes those elements by definition. Finally, it was not appropriate to use standardized frailty definitions in our analyses because in the frailty definitions that we have published in the past, malnutrition risk is a defining factor [30,31]. Instead, we used measures of functional capacity and comorbidity which do not include malnutrition indices.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the functional independence and the comorbidities of the patients are outweighed by ASA physical status which largely includes those elements by definition. Finally, it was not appropriate to use standardized frailty definitions in our analyses because in the frailty definitions that we have published in the past, malnutrition risk is a defining factor [30,31]. Instead, we used measures of functional capacity and comorbidity which do not include malnutrition indices.…”
Section: Discussionmentioning
confidence: 99%
“…59,68 Complications Fifty studies reported outcome data for postoperative complications (total n = 31,408; Supplemental Digital Content, table 3, http://links.lww.com/ALN/C333). [30][31][32][33][34][36][37][38][39][41][42][43][45][46][47][48]51,[53][54][55][56]58,60,63,64,66,69,71,[73][74][75][76][80][81][82]84,86,88,89,91,[94][95][96][97][98][99][100][101] Eight studies reported postoperative complication data for ...…”
Section: Accuracy and Feasibility Of Frailty Instrumentsmentioning
confidence: 99%
“…Thirty-two studies reported aspects of feasibility. 6,39,46,55,56,60,[63][64][65]67,68,70,[76][77][78][82][83][84]86,92,93 Findings are summarized in table 3 (full details in Supplemental Digital Content, table 8, http://links.lww.com/ALN/C333); only 19 of 50 available data points were based on objective data, compared to 31 of 50 that were subjectively supported. Overall, the Clinical Frailty Scale, Edmonton Frail Scale, Frailty Index, and Fried Phenotype had the largest amounts of available data.…”
Section: Feasibilitymentioning
confidence: 99%
“…16 Only a few studies have compared preoperative frailty models in predicting postoperative outcomes. 17 To date and to the best of our knowledge, no study has yet performed a comparison of these three frailty evaluation methods (FRAIL, FI and CFS), especially in China, in patients undergoing elective abdominal surgery. There are different ways to define and assess frailty, leading to prevalence rates ranging from 25% to 46%.…”
Section: Discussionmentioning
confidence: 99%